Anaerobic Wastewater Treatments: Prediction of Retention Time on RT/RW Plant - Sari, Dessy Agustina; Sukanta, Sukanta; Hakiim, Azafilmi (International Series on Interdisciplinary Science and Technology, 2018)
Wastewater treatment gave major problem in higher of chemical oxygen demand that backgrounded by amount and type of PT RT/RW products. The waste was polymer, mixture of nitrogen, mixture of phosphate, and oil. This factory used active sludge and microorganism (anaerobic condition). Research result showed that pH ranged 4,94 until 8,02. This data gave a decreasing sharply in acidic condition. The thing could be caused acetogenic phase in area pond anaerobic. The phenomenon might be recited because possibility of biologist living this waste did not take place as well and or could give deathly affect to the anaerobic bacteria. Customary pH for the bacteria was 6,8 – 7,4. Temperature data reached 28-33oC so their activities were good. Then, efficiency of anaerobic wastewater treatment was 62,95 to 66,06%. The data indicated that the research was not accordance with SOP companies. Inlet concentration of chemical oxygen demand had variation and gave unbalancing affect to digestive bacteria load. Estimation to get valid COD was 11-14 days. The duration was required by the microorganism to digest the matter organic perfectly to be methane and carbon dioxide gas.